Keterlibatan Orang Tua dalam Menumbuhkan Minat Anak untuk Melanjutkan Bisnis Keluarga - Jefry Aulia Martha; Rachmad Hidayat; Andy Prasetyo Wati; Nur Khulfi Mahwanda Sari (STKIP PGRI SITUBONDO, 2021)
This study aims to determine the involvement of parents in fostering children's interest in continuing the family business by providing entrepreneurial education that contains entrepreneurial values. Qualitative phenomenological research design is used to this study, the main informants in the study consisted of 3 legendary culinary business owner in Malang and 3 children who owned the legendary culinary business in Malang. The result of this study can be describe as follow: (1) parents have provide entrepreneurship education by providing entrepreneurship education that contains entrepreneurial values to foster children’s interest in continuing family business that is, self-confidence, responsibility, dare to take risk, optimism, future-oriented, disciplined, honest, leadership, creative, and innovative. (2 parents provide entrepreneurship education that contains entrepreneurial values by involving children to help manage the family business and provide examples of how to manage a family-run business, because the children here will see what is done by parents. (3 parents provide democratic education, where children have given their freedom to choose a career that is of interest by full supervision and guidance from the parents.